Negotiating parenting practices: the arguments and justifications of Finnish couples. (1st March 2021) - Eerola, Petteri; Närvi, Johanna; Terävä, Johanna; Repo, Katja
Abstract : This article explores Finnish different-sex couples' ( n = 12) negotiations on their parental division of labour. Theoretically, the article is based on the literature on gendered parenting practices and relational negotiations. Our discourse analysis reveals how the couples produced 'togetherness' and 'our family' by representing their care practices as agreements, irrespective of whether the care was described as equally shared or distinctly gendered. Disagreements reflecting more individualistic tones, and mainly resulting from the mothers' sense of unfairness, were especially foregrounded when the distribution of household duties was discussed. The analysis also revealed how men cited involved fatherhood as a justification for their lesser responsibility for housework, while women sought to reconcile the contradictory discourses of equal parenting and mother's primacy. Our results show how personal wishes and preferences, work life, family policies and cultural discourses are reflected in couples' negotiations on parenting practices and moral identities pertaining to 'good' motherhood and fatherhood.